2019
DOI: 10.1021/acs.jpca.8b11333
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Synchrotron Spectroscopy and Quantum Chemical Calculations of the Potentially Important Interstellar Molecule, 2-Chloroethanol

Abstract: The high brightness of the Australian synchrotron allowed for detailed spectra to be collected at high resolution (0.00096 cm −1 ) in the vicinity of the a/b/c-type ν 19 band of 2-chloroethanol, which involves O−H torsional motion about the C−O bond. A rovibrational analysis was performed for both chlorine isotopologues in the ν 19 fundamental (centered at ∼344 cm −1 ) which involved the assignment of 7153 lines (J ≤ 90, K a ≤ 41). A global fit to these lines in addition to 119 microwave lines (J ≤ 29, K a ≤ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
(94 reference statements)
4
7
0
Order By: Relevance
“…The successful production of monodeuterated 2-chloroethanol is evident from the shift in the ν 20 torsional band of the most stable rotamer of 2-chloroethanol (Gg′); , this shift is from 344.2 to 240.6 cm –1 , which is consistent with the relation, = 243 cm –1 . As shown in Figure , we observed a marked gradual decrease in the deuterated 2-chloroethanol precursor peak as we increased the pyrolysis temperature from 800 to 950 °C.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The successful production of monodeuterated 2-chloroethanol is evident from the shift in the ν 20 torsional band of the most stable rotamer of 2-chloroethanol (Gg′); , this shift is from 344.2 to 240.6 cm –1 , which is consistent with the relation, = 243 cm –1 . As shown in Figure , we observed a marked gradual decrease in the deuterated 2-chloroethanol precursor peak as we increased the pyrolysis temperature from 800 to 950 °C.…”
Section: Resultssupporting
confidence: 73%
“…Band Assignment and Torsional Analysis. The successful production of monodeuterated 2-chloroethanol is evident from the shift in the ν 20 torsional band of the most stable rotamer of 2-chloroethanol (Gg′); 41,42 this shift is from 344.2 to 240.6 cm −1 , which is consistent with the relation,…”
Section: Methodssupporting
confidence: 80%
“…It is clear from this figure that the most affected band is the HOC torsion plus OH stretching combination band appearing in the far-infrared below 500 cm –1 . In our ωB97X-D/cc-pVTZ calculations, the band appears at 376 cm –1 for the Gg′ rotamer, while experimentally it was recorded at 344.0 cm –1 by Durig et al and 344.2 cm –1 by Soliday et al The analogous bands in Tg and Tt were obtained by us at 326 and 290 cm –1 respectively, while Durig et al reported them experimentally at 281 and 200 cm –1 , respectively. The discrepancy between our values and the experimental ones is probably due to anharmonic effects.…”
Section: Resultsmentioning
confidence: 70%
“…This barrier, corresponding to the transition state TS12, is however 15% larger than the barrier for the transformation of 2ClEtOH to anti -VA (57.1 vs 48.7 kcal mol –1 ). The reverse barrier (i.e., that for the reaction HCl + HOCH 2 CH 2 OH → ClCH 2 CH 2 OH + H 2 O) was calculated simultaneously to this work by Soliday et al, who found a value of 52 kcal mol –1 at the MP2/cc-pVTZ level, in agreement with our own value of 53.4 kcal mol –1 .…”
Section: Resultsmentioning
confidence: 99%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%